Optimizing Principal Management for Deep Learning Curriculum Implementation in Vocational High Schools - Sutikno, Sutikno (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The present study aims to analyze the strengths, weaknesses, opportunities, and threats of school principals’ management in implementing the deep learning curriculum in vocational schools and to formulate strategic recommendations through a SWOT analysis. The current research employs a qualitative approach with a multisite case study design involving Vocational High Schools (SMK) in Central Java Province. The study population consisted of approximately 1,547 SMK principals across the province, while the research sample comprised 45 principals representing both public and private schools. Data were collected through in-depth interviews with school principals as the main informants. The analysis was conducted with thematic coding to classify the data into strengths, weaknesses, opportunities, and threats, then synthesized in an operational SWOT matrix to formulate strategic recommendations. The results suggest that the principal has strategic leadership, builds a school culture that is open to innovation, and utilizes available facilities to support the implementation of deep learning. However, internal weaknesses were found in a dense, rigid curriculum, sporadic teacher training, limited technological infrastructure, and traditional assessment practices. The external side, government policies, partnership opportunities with industry and universities, and the demands of 21st-century competencies are important opportunities. Meanwhile, students' socio-economic disparities, uneven technological readiness, and fluctuating external support are real threats. The results confirm that strategic planning based on SWOT analysis can help principals maximize strengths and opportunities, while systematically addressing weaknesses and threats. The research findings are expected to be a reference for school principals, teachers, and policymakers.